Age Differences in Electronic Mental Health Literacy: Qualitative Study - Richard Huan Xu; Lidan Tian; Liling Zhu; Yuan Cao; Sherry Kit-wa Chan; Dong Dong; Wai-ling Annie Cheung; Eliza Lai-yi Wong (JMIR Publications, 2024)
BackgroundElectronic mental health literacy (eMHL) is critical for accessing and effectively using digital mental health resources. However, there is a paucity of research on how eMHL varies across age groups. ObjectiveThis study aimed to investigate differences in eMHL among young, middle-aged, and older adults; provide insights into the needs, behaviors, and attitudes of different age groups in relation to digital mental health resources; and ultimately, inform the improvement of mental health services. MethodsA qualitative investigation was conducted to examine the differences in eMHL across different age demographics in the Chinese population in 2023. The study sample comprised 3 distinct age groups: 18-34 years, 35-64 years, and 65 years and older. Participants were recruited through purposive sampling to ensure a diverse representation of the population. Data were collected through semistructured one-on-one interviews, which allowed for in-depth exploration of individual experiences and perceptions. The gathered data were subsequently subjected to rigorous thematic analysis to enable the identification and interpretation of recurring patterns and themes. ResultsThe principal outcomes derived from these interviews were synthesized into 5 distinct dimensions: emotional needs, use of digital mental health resources, assessment of digital mental health information, engagement with social media to regulate emotions, and coping strategies. These dimensions were uniformly observed across the 3 age groups. ConclusionsWe identified differences in knowledge, skills, and attitudes regarding the use of web-based information for managing mental health problems between the 3 age groups. The findings highlight the importance of age-specific strategies for improving eMHL.